The incidence of asymptomatic hypoglycemia in term newborn babies weighing more than two kilograms - Thirumalaikumarasamy, Sivaraman; Ramalingam, Ezhilarasu; Sachithanantha Moorthi, Mani Madhavan; Nadesan, Balakrishnan (International Journal of Contemporary Pediatrics, 2017)
Background: Neonatal hypoglycemia is a common metabolic problem especially in cases like prematurity, sepsis and small gestational age. Episodes of asymptomatic hypoglycemia may occur due to many risk factors. The present study aimed to evaluate the incidence of asymptomatic hypoglycemia in term new born babies weighing more than 2 kg, to study the plasma sugar level at various time points during first 48 hours of life and to study the effect of maternal factors like parity, mode of delivery, glucose infusion during labour, and time since last feed on plasma sugar level. Methods: A hospital based longitudinal study was conducted over a period of one year from April 2005 to March 2006 in Kilpauk Medical College Hospital, Chennai. 400 babies born of consecutive deliveries were included in the study. Their plasma glucose levels were assessed in cord blood, 3 hr, 12 hr and 36 hr of life. Plasma glucose levels were analysed with regards to distribution, variables like parity, mode of delivery, dextrose infusion during labour and time since last feed. The plasma glucose levels were statistically analysed by paired student ‘t’ test, multiple analysis of variance (ANOVA), chi- square test using SPSS (version 7.5) statistical package. Results: The overall incidence of hypoglycemia was seen in 20% of the neonate’s in which 29.7% in small gestational age (SGA) and 16.7% in appropriate gestational age (AGA) babies. A significant (p <0.01) association between hypoglycemia and birth weight was observed. The association between hypoglycemia with parity, mode of delivery, sex of the baby and glucose infusion received by the mother was studied, but no significant association was found. A significant difference in plasma glucose based on birth weight at 3rd hour, 12th hour and 36th hour was observed (p <0.05). None of the infants showed any clinical signs of hypoglycemia. Conclusions: The incidence of hypoglycemia was noted in 20% of the neonates. Low birth weight was considered as risk factor. A significant association was also observed between plasma glucose, mode of delivery and time since last fed.